Studi Perbandingan Biaya pada Pekerjaan Pembongkaran Balok Girder di Proyek Penggantian Jembatan Cinagara - Suhendar, Tatang; Mardiaman, Mardiaman; Azhar, Moh; Taqwa, Fadhila Muhammad Libasut (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
There are 3 (three) alternative methods for dismantling bridge girders in the Cinagara Bridge replacement project, to find the most efficient and safe approach. The Cinagara Bridge, which is on the Ciawi – Sukabumi national road, Caringin district, Bogor Regency, located in a densely populated area and also close to the installation of the PGN pipeline network and PLN cable lines. This research aims to choose the implementation method with the most efficient costs, while still paying attention to safety and ease of work. The three alternative methods are: dismantling by lifting and moving the girder beam as a whole; dismantling by lifting the girder beam as a whole, then moving it segment by segment; and dismantling by breaking the girder beams on the spot and dropping them into the river, to be then moved outside the site. The research results show that the third method, namely breaking the girder beam on the spot and dropping it into the river, has the lowest implementation cost of IDR 86,637,250.00 and efficient implementation time. This method also ensures that the demolition results can be mobilized outside the project site and has the lowest risk of accidents. The first and second methods cost IDR 365,762,935.00 and IDR 170,301,233.00 respectively, and face various technical challenges and social risks. This research provides recommendations for using the third method with appropriate adjustments to ensure a smooth dismantling process, minimize environmental impacts, and maximize work safety. Apart from that, it is important to carry out routine equipment inspections, arrange demolition times during the day, and install safety nets to protect the surrounding area from demolition debris. Thus, this research can be a reference in choosing an effective demolition method for similar projects